A community-based prediabetes knowledge assessment among Saudi adults in Al-Ahsa region, 2018 - Essa AlSaleh; Morad Alnaser; Ali Alsalman; Abdullah ALRamdhan; Husein Alsalman; Ola Alhamrani; Alaa Alhamrani; Muntadher AlSaleh; Tahani AlEithan; Khawla AlArfaj; Hussain Al Sunayhir; Mujtaba AlSaleh (SAGE Publishing, 2021)
Background: Prediabetes has been considered to be a reversible condition; a modification of lifestyle and other intervention can be successfully applied during the prediabetes period to prevent the development of type 2 diabetes. The purpose of the present study was to assess knowledge of prediabetes and its risk factors for the community in the Al-Ahsa region. Design and method: A cross-sectional community-based study was conducted in the Al-Ahsa region from mid-to-late December 2018. A sample size of 812 was determined using a single-proportion formula. Results: Of the 812 respondents who gave consent to participate in the interview; the male to female ratio was 1.1:1. 13.2% of the respondents reported that they had diabetes. Among the respondents, 87.1% had a high level of knowledge of prediabetes, while 12.9% had low-to-moderate knowledge. 84% of males 40 years of age or older, 88.7% (384) of people with university or higher education, and 95.1% (78) of people who worked as health practitioners had high knowledge of prediabetes.Overall, there was a statistically significant association between age and prediabetes knowledge (𝑥2 =5.006, p=0.025). Occupation also showed a significant statistical association with prediabetes knowledge (𝑥2 =9.85, p=0.02). Conclusion: Knowledge is considered an important factor in the prevention of prediabetes and diabetes. People in Al-Ahsa demonstrated a high level of knowledge regarding some risk factors for prediabetes. However, there were a number of deficiencies in the knowledge of prediabetes risk factors and preventive measures as well as in general knowledge of prediabetes, which may lead to a high prevalence of prediabetes and diabetes.